The Role of Disgust in Male Sexual Decision-Making - Oaten, Megan; Stevenson, Richard J.; Tapp, Caley; Case, Trevor I.; Cousins, Allie (Frontiers in Psychology, 2019)
Sexual arousal is known to increase risky behaviours, such as having unprotected sex. This may in part relate to the emotion of disgust, which normally serves a disease avoidant function, and is suppressed by sexual arousal. In this report we examine disgust's role in sexual decision-making. Male participants received two study packets that were to be completed at home across two different time-points. Participants were asked to complete one packet in a sexually aroused state and the other in a non-aroused state. Participants were asked to rate: (1) arousal, (2) disgust, (3) willingness for sex, and (4) disease risk toward a range of female targets, which varied in level of potential disease risk (sex-worker vs. non sex-worker) and attractiveness. A measure of trait disgust was also included along with other related scales. Sexual arousal was associated with reduced disgust and reduced judgments of disease risk for all targets - these latter two variables being correlated - and with enhanced willingness to have sex with all of the depicted persons. Willingness to have sex when aroused (in contrast to non-aroused) was predicted by disease risk judgments and trait disgust, suggesting both direct (state) and indirect (trait) effects of disgust on sexual decision-making.